2020
DOI: 10.1186/s12889-020-09662-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of medical equipment in the spread of nosocomial infections: a cross-sectional study in four tertiary public health facilities in Uganda

Abstract: Background With many medical equipment in hospitals coming in direct contact with healthcare workers, patients, technicians, cleaners and sometimes care givers, it is important to pay close attention to their capacity in harboring potentially harmful pathogens. The goal of this study was to assess the role that medical equipment may potentially play in hospital acquired infections in four public health facilities in Uganda. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Hospital hygiene is already challenging in SSA and requires massive coordination of consumables, training, and monitoring. (Ssekitoleko et al 2020) Integrating hygiene awareness into POCUS training could be an opportunity to contribute to this critical issue.…”
Section: Nosocomial Fomite-borne Transmissionmentioning
confidence: 99%
“…Hospital hygiene is already challenging in SSA and requires massive coordination of consumables, training, and monitoring. (Ssekitoleko et al 2020) Integrating hygiene awareness into POCUS training could be an opportunity to contribute to this critical issue.…”
Section: Nosocomial Fomite-borne Transmissionmentioning
confidence: 99%
“…Where sepsis is more promptly recognised, and where healthcare workers have a high degree of suspicion of the diagnosis, the corollary is an increased use of antimicrobials and inevitably emerging drug resistance to first-line antibiotics such as amoxicillin, chloramphenicol and co-trimoxazole [ 52 ]. When identified early and treated timely with antibiotics, sepsis fatality risk is reduced, but it usually results in high antibiotic usage [ 8 , 47 , 54 , 55 ], leading to AMR, which is now a serious global public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 1 out of 10 patients gets infected by nosocomial infection [6]. During hospitalization, these infections can be transmitted to patients by healthcare workers, other patients, hospital equipment, or interventional procedures [7].…”
Section: Introductionmentioning
confidence: 99%